NIET ONTVANKELIJKE VERKLAARD DALAM PUTUSAN - PUSPITANINGRAT, I DEWA AGUNG AYU MAS; Kayuan, Putu Chandra Kinandana; Rimbawa, I Made Artha (Fakultas Hukum Universitas Ngurah Rai, 2024)
In addition, a lawsuit can be terminated (Niet Ontvankelijke Verklaard) NO if the object of the lawsuit is not clear, then the claim cannot be accepted. The issues raised from this paper are: (1) Formal defects in the lawsuit, and (2) Judge's consideration in deciding an inadmissible lawsuit (Niet Ontvankelijke Verklaard) in case Number : 817/Pdt.G/2023/PN Dps. This research includes doctrinal research that uses primary legal data/materials, secondary legal data/materials and tertiary legal data/materials. The technique of collecting data/legal materials is carried out with a card system and uses a statutory approach, a fact approach, and a conceptual analysis approach. The results in this study are: Judges in examining and trying cases. The judge will assess whether the lawsuit has met the formal and material requirements. Parameters for assessing formal requirements, for example about the competence of the court both absolute competence and relative competence, whether the case submitted falls within the jurisdiction of the court or not (relative competence), or whether the case falls within the scope of the court's authority (absolute competence). Decisions niet ontvankelijke verklaard or